Petit de Bachaumont - Tate, R (Voltaire Foundation, 2017)
Introduction I. Bachaumont's early life 1. Family and birth 2. Influence of Le Nôtre 3. Some intellectual tendencies II. Three friends of Bachaumont 1. The abbé Prévost 2. The abbé Gédoyn 3. A Protégé - the marquis d'Eguilles III. Bachaumont's aesthetic pursuits 1. Painting and sculpture 2. Music 3. Architecture and urbanisme IV. The salon of Madame Doublet 1. Bachaumont and Madame Doublet 2. The Habitués 3. Character of the salon V. The Nouvelles à la main 1. Background 2. The Two Registres and their yield 3. Decline of the salon VI. The Mémoires secrets 1. Publication 2. Reception 3. The Mémoires secrets and the parlements Conclusion Works cited